Pengaruh Model Pembelajaran Quantum Teaching Terhadap Kemampuan Pemahaman Konsep Matematis Siswa Pada Materi Perbandingan Kelas VII - Ayu Indriani; Nurul Husna; Mariyam Mariyam (Journal on Education, 2024)
This research aims to determine whether or not there is an influence of the Quantum Teaching learning model on students' ability to understand mathematical concepts. This research method is an experiment with a quantitative approach. The population in this study were all class VII students of Singkawang 1 Public Middle School. The sampling technique in this research was Post-test Only Control Group Design. The sample in this research was class VII D students at SMP Negeri 1 Singkawang. Data was obtained through test instruments for the ability to understand mathematical concepts as well as questionnaires for student independence and student activities. The material used in the ability test to understand mathematical concepts is Comparison material. The sampling technique in this research is Cluster random sampling. The results of the research show: 1) There is a difference in the ability to understand mathematical concepts between students who receive Quantum Teaching Model learning and students who receive direct learning models in Comparative material for class VII SMP Negeri 1 Singkawang. This was proven by using normality test techniques, homogeneity tests, and t tests for two independent samples. 2) there is a difference in the ability to think creatively in mathematics between students who receive Quantum Teaching Model learning and students who receive direct learning models in comparative material for class VII SMP Negeri 1 Singkawang. This is proven by using the Effect Size formula. 3) Student activities are classified as active in learning the Quantum Teaching Model. This is proven by the formula for the percentage of student activity frequency. 4) student independence is relatively good with the application of the quantum teaching learning model. This is proven by analyzing the scores obtained by students.